2006
DOI: 10.1128/aem.72.3.2191-2199.2006
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Novel-Substrate-Accepting Biphenyl Dioxygenases through Segmental Random Mutagenesis and Identification of Residues Involved in Enzyme Specificity

Abstract: Aryl-hydroxylating dioxygenases are of interest for the degradation of persistant aromatic pollutants, such as polychlorobiphenyls (PCBs), or as catalysts for the functionalization of aromatic scaffolds. In order to achieve dioxygenation of technical mixtures of PCBs, enzymes with broadened or altered substrate ranges are essential. To alter the substrate specificity of the biphenyl dioxygenase (BphA) of Burkholderia xenovorans LB400, we applied a directed evolution approach that used structure-function relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
(49 reference statements)
1
22
0
Order By: Relevance
“…First, as shown in previous publications (15,42) as well as in the present work, its substrate range frequently is narrower than that of subsequent pathway enzymes. Second, its regiospecificity of dioxygenation is a critical parameter, as it determines the (potential) site(s) of attack by the subsequent enzymes of the metabolic route (Fig.…”
supporting
confidence: 49%
“…First, as shown in previous publications (15,42) as well as in the present work, its substrate range frequently is narrower than that of subsequent pathway enzymes. Second, its regiospecificity of dioxygenation is a critical parameter, as it determines the (potential) site(s) of attack by the subsequent enzymes of the metabolic route (Fig.…”
supporting
confidence: 49%
“…Altogether, the observation made regarding the catalytic features of the variant BphAEs obtained in this investigation brings to mind that changing substrate specificity is a complex process; as pointed out recently by Zielinski et al (37), it not only involves amino acid residues that interact directly with the substrate, but it also involves residues that are not part of the pocket lining and that are not predictable through structural modeling. These residues might indirectly influence the shape of the catalytic pocket or the conformation of the residues that are involved in substrate binding and positioning inside the catalytic pocket.…”
Section: Discussionmentioning
confidence: 97%
“…The strains producing the prototype enzymes BphA WB15h and BphA WC18h were assayed for dioxygenation of 10 CBs that were major, minor, or not constituents of the PCB mixture found at the Wittenberg site. It had previously been shown that the BphB and BphC enzymes, which were also synthesized by the recombinant strains, were able to convert ortho,meta-dioxygenated products of all of these CBs into MCPs (33,34,43). Initial dioxygenations that formed this type of further degradable catabolites were termed "productive."…”
Section: Resultsmentioning
confidence: 99%
“…It belongs to class II of aryl-hydroxylating dioxygenases (ARHDOs) that typically hydroxylate substituted benzenes, like toluenes and biphenyls (7). This enzyme represents a catabolic bottleneck, as its substrate range is typically narrower than that of subsequent pathway enzymes (9,13,43). Moreover, its regiospecificity is a crucial parameter, as it codetermines whether the initial dioxygenation products become dead-end metabolites or can be further transformed.…”
mentioning
confidence: 99%
See 1 more Smart Citation